Sustained Effectiveness of Secukinumab Across Different Body Regions in Patients with Moderate-to-Severe Plaque Psoriasis from the PURE Registry - Gooderham, Melinda; Papp, Kim A.; Lynde, Charles; Delorme, Isabelle; Beecker, Jennifer; Albrecht, Lorne; Dei-Cas, Ignacio; Brassard, Danielle; Prajapati, Vimal H.; Vieira, Antonio; Rihakova, Lenka (Université d'Ottawa | University of Ottawa, 2022)
Abstract Introduction The association between physician-reported and patient-reported outcomes in patients with psoriasis is not adequately explored. Trends in PASI scores across body regions and the descriptive correspondence between physician-reported PASI components and patient-reported Psoriasis Symptom Diary are reported here. Methods PURE is a prospective observational study in adult patients from Canada and Latin America with moderate-to-severe chronic plaque psoriasis. The study enrolled 2362 adult patients treated with secukinumab versus other approved therapies (1:1 ratio). The PASI total score, PASI sub-scores for erythema, thickening, and scaling, and PASI scores for each body region were evaluated and further correlated with disease impact using the Psoriasis Symptom Diary. Results Secukinumab treatment showed early reduction in the PASI total score (mean ± SD) from 13.3 ± 9.02 at baseline to 2.3 ± 3.99 at 3 months; a similar trend was observed for PASI sub-scores for erythema (4.8 ± 3.21 to 0.9 ± 1.44), thickening (4.3 ± 3.00 to 0.7 ± 1.33) and scaling (4.2 ± 3.04 to 0.7 ± 1.30). The reduction in PASI total and sub-scores were sustained up to 36 months. Psoriasis Symptom Diary component scores related to redness, cracking, and scaling showed a similar reduction from baseline at 3 months that was also sustained up to 36 months. PASI regional scores for each body region showed reduction at 3 months with disease in the lower limbs being more treatment resistant. Safety profile of secukinumab was consistent with its established safety profile without any new or unexpected signals. Conclusions Overall, an early and sustained resolution of erythema, thickening, and scaling was observed. Improvements were evident across all body regions, with the most persistent disease seen in the lower limbs. Trends in disease severity, as assessed by physicians using PASI, broadly reflected the trend in the comparable questions of the Psoriasis Symptom Diary assessed by patients.